Acute Effects of Implantable Cardioverter‐Defibrillator Shocks on Biomarkers of Myocardial Injury, Apoptosis, Heart Failure, and Systemic Inflammation. Issue 4 (8th March 2017) - BREWSTER, JORDAN; SEXTON, TRAVIS; DHALIWAL, GARY; CHARNIGO, RICHARD; MORALES, GUSTAVO; PARROTT, KEVIN; DARRAT, YOUSEF; GURLEY, JOHN; SMYTH, SUSAN; ELAYI, CLAUDE S.
Abstract : Background: Implantable cardioverter‐defibrillator (ICD) shocks are potentially associated with myocardial injury, altered hemodynamics, apoptosis, and inflammatory signaling. Their precise cellular impact can be explored after defibrillation testing (DFT) via biomarkers. We evaluated changes in biomarkers after ICD shocks during DFT. Methods: We prospectively enrolled outpatients presenting for first implantation of a cardiac device. Biomarkers indicative of myocardial injury, inflammation, and apoptosis were measured before and after implantation, and compared between patients receiving DFT (DFT+) to those not (DFT−). Results: Sixty‐three patients were enrolled, 40 in the DFT+ group and 23 in the DFT− group. Average levels of troponin I, hsCRP, Calprotectin, N‐terminal pro B‐type natriuretic peptide (NTproBNP), and sFas increased by >50% after cardiac device implantation compared to baseline. Increase in troponin never exceeded the 50‐fold upper limit of normal (2 ng/mL). Troponin trended higher in the DFT+ group at 8 hours (median 0.18 ng/mL, interquartile range [IQR] 0.11–0.48) versus the DFT− group (0.10 ng/mL, IQR 0.06–0.28, P = 0.0501); NTproBNP had a similar trend (P = 0.0581). sFas significantly increased in the DFT+ group from baseline (median 4663 pg/mL, IQR 2908–5679) to 24 hours (5039 pg/mL, IQR 3274–6261; P = 0.0338) but not in the DFT− group (P = 0.4705). Conclusion: DFT testing is associated with acutely increased plasma levels of troponin and sFas, a biomarker of apoptosis, along with a trend toward higher NTproBNP.